PENGGUNAAN MEREK KOLEKTIF SEBAGAI ALTERNATIF PERLINDUNGAN MEREK BAGI KEPENTINGAN BERSAMA (STUDI KASUS MEREK GENTENG SOKKA KEBUMEN ) - Mastur . (Qistie Jurnal Ilmu Hukum, 2011)
On the global and free trade era, mark has urgent role on determining equalregulation system because the system could be prevented if there is fair and healthcompetitive business. Genteng Sokka, merek of tile from Kebumen, is one itemexample.The matter in this research is if collective mark could be used as marklaw protection alternative, and response of Kebumen regent government on theusing of it. The meant of the research is to know and analysis using of collectivemark as mark law protection alternative , how the regent government on thecollective mark. The research used empiris yurisdical method with specificationanalytic description, the writer explain abaout mmrk collective making as thealternative so it could decrease of competitive level, and ho regent governmentattitude this mark. From the research, could be argued if the collective mark couldbe used as alternative, because the property is owned by small mediumenterprises, non fair competitive among the owners could limited. Thecontribution to devolepment is significant employment and investment so gentengSokka could be potencial industry in Kebumen Regent.Dissemination the urgentof protection mark must be done so every owner of genteng Sokka couldunderstand how urgent of protection.Key words : Protection mark, collective mark, protection mark alternative